Aortic injury from thoracic vertebral stabilization instrument - Burma, O.; Rahman, A.; Çkirdekçi, A.; Uyar, I.S.; Topsakal, C. (Asia Publishing Exchange Pte Ltd, 2001)
A case of delayed postoperative thoracic aortic rupture from erosion by a spinal fixation device is described to call attention to this potential catastrophe. Appropriate management and prevention of this complication is discussed.
Keywords: politef; adult; aorta injury; aorta rupture; article; bone prosthesis; case report; chordoma; erosion; female; human; medical instrumentation; plate fixation; prosthesis fixation; thoracic spine; vertebra